Unified Total Synthesis of 3‐epi‐Ryanodol, Cinnzeylanol, Cinncassiols A and B, and Structural Revision of Natural Ryanodol and Cinnacasol. Issue 7 (14th January 2016) - Koshimizu, Masaki; Nagatomo, Masanori; Inoue, Masayuki
Abstract: Ryanodane diterpenoids structurally share an extremely complex fused ring system, but differ in the substitution patterns of the hydroxy groups. Since these congeners exhibit various biologically important functions, their efficient chemical constructions have been greatly anticipated. We previously accomplished the total synthesis of ryanodine (1 ) using pentacycle8 as the advanced intermediate. Here, we report the unified total syntheses of four distinct diterpenoids, 3‐ epi ‐ryanodol (3 ), cinnzeylanol (4 ), cinncassiols B (5 ), and A (6 ), from8, all within 10 steps. A series of highly optimized chemo‐ and stereoselective reactions and protecting‐group manipulations enabled assembly of the densely oxygenated structures of3 –6 . Furthermore, the present synthetic studies established the C13 S stereochemisty of5 –7 and revised the proposed structures of natural ryanodol (2 ) and cinnacasol (7 ) to be those of3 and6, respectively. Abstract : Ryanodane diterpenoids have an extremely complex fused ring system with distinct positions and orientations of the oxygen‐based functionalities. Reported is the unified total syntheses of four diterpenoids, 3‐ epi ‐ryanodol, cinnzeylanol, and cinncassiols B and A, from a common pentacycle. This work also served to revise the proposed structures of natural ryanodol and cinnacasol to be those of 3‐ epi ‐ryanodol and cinncassiol A, respectively.